The development of a disclosure framework for tangible heritage asset in the financial reporting of the Malaysian public sector / Mohamad Hafiz Rosli - Rosli, Mohamad Hafiz (2024)
Accounting for Heritage Asset (HA) is always in the interest of many accounting researchers and has become a concern for public sector entities and the International Public Sector Accounting Standards Board (IPSASB). The accounting issues of HA focus on the recognition, measurement, and disclosure. The present accounting standards for HA namely the International Public Sector Accounting Standards (IPSAS) locally known as Malaysian Public Sector Accounting Standard (MPSAS) 17 Property, Plant and Equipment unable to reflect the significance and importance of the HA resulted in difficulties in incorporating HA into the public sector’s financial statement. HA possesses unique characteristics such as being priceless, irreplaceable, and rare making it important to the country’s history, culture and society. This study provides a suitable Tangible HA Disclosure Index, combining financial information and nonfinancial information of the HA. In addition, this study also describes the issues and challenges in accounting for HA faced by the Malaysian Government Agencies in Malaysia. This study adopts an exploratory sequential mixed-method research approach, beginning with a qualitative approach and followed by a quantitative approach. Data were collected through individual face-to-face interviews, document reviews, and a survey questionnaire.